2022
DOI: 10.1101/2022.01.11.21268036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening for SARS-CoV-2 persistence in Long COVID patients using sniffer dogs and scents from axillary sweats samples

Abstract: Objectives: Dogs can be trained to identify several substances not detected by humans, corresponding to specific volatile organic compounds (VOCs). The presence of VOCs, triggered by SARS-CoV-2 infection, was tested in sweat from Long COVID patients. Patients and methods: An axillary sweat sample of Long COVID patients and of COVID-19 negative, asymptomatic individuals was taken at home to avoid any hospital contact. Swabs were randomly placed in olfaction detection cones, and the material sniffed by at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…In other words, when acute COVID-19 samples are presented next to Long COVID samples the dogs rather indicate the samples from acute cases, with the smell they were trained on. In a recently published study performed by Grandjean et al, dogs identified only 51.5% of Long COVID patients when they were presented next to healthy individuals ( 20 ). The lower percentage of identified Long COVID patients compared to our results (51.5 vs. 92.86%) might be explained by the differing sample quality as the samples used by Grandjean et al were taken at home and were sent via mail without standardized freezing or cooling of the samples ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, when acute COVID-19 samples are presented next to Long COVID samples the dogs rather indicate the samples from acute cases, with the smell they were trained on. In a recently published study performed by Grandjean et al, dogs identified only 51.5% of Long COVID patients when they were presented next to healthy individuals ( 20 ). The lower percentage of identified Long COVID patients compared to our results (51.5 vs. 92.86%) might be explained by the differing sample quality as the samples used by Grandjean et al were taken at home and were sent via mail without standardized freezing or cooling of the samples ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study performed by Grandjean et al, dogs identified only 51.5% of Long COVID patients when they were presented next to healthy individuals ( 20 ). The lower percentage of identified Long COVID patients compared to our results (51.5 vs. 92.86%) might be explained by the differing sample quality as the samples used by Grandjean et al were taken at home and were sent via mail without standardized freezing or cooling of the samples ( 20 ). Nevertheless, these results also support the hypothesis that the disease-specific odor of acute COVID-19 is still present in the majority of Long COVID samples, but probably not as strong as in samples of acutely infected COVID-19 patients ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the ability of medical scent detection dogs to identify samples from SARS-CoV-2 infected individuals with high accuracy, highlighting the role such dogs could play in the management of a pandemic. [1][2][3][4][5][6][7][8][9][10][11][12][13] Previous research showed that different body fluids, such as saliva, sweat and urine and other sample types like worn face masks are suitable for detection,…”
Section: Introductionmentioning
confidence: 99%
“…The use of rapid point of care antigen-tests (PoC-antigen tests) for the diagnosis of a SARS-CoV-2 infection continues to be a key tool to manage the ongoing COVID-19 pandemic. Several studies have shown the ability of medical scent detection dogs to identify samples from SARS-CoV-2 infected individuals with high accuracy, highlighting the role such dogs could play in the management of a pandemic 1–13. Previous research showed that different body fluids, such as saliva, sweat and urine and other sample types like worn face masks are suitable for detection, which suggests that there is a general SARS-CoV-2 infection associated odour that dogs can be trained on 14–16.…”
Section: Introductionmentioning
confidence: 99%
“…According to varied studies, a high level of antibodies either appears to be protective [7] or, conversely, to be associated with higher persisting symptoms [7, 8]. So far, the underlying mechanisms of these symptoms remain unclear: the persistence of viral RNA and/or proteins has been demonstrated in some cases in Long COVID patients [10, 11, 12, 13, 14, 15; 16]. To date, it is not known whether this genetic or protein material persistence corresponds to a replicating virus or not.…”
Section: Introductionmentioning
confidence: 99%